2010
DOI: 10.1364/ao.49.006675
|View full text |Cite
|
Sign up to set email alerts
|

Midinfrared broadband achromatic astronomical beam combiner for nulling interferometry

Abstract: Integrated optic beam combiners offer many advantages over conventional bulk optic implementations for astronomical imaging. To date, integrated optic beam combiners have only been demonstrated at operating wavelengths below 4 µm. Operation in mid-infrared wavelength region, however, is highly desirable. In this paper, a theoretical design technique based on three coupled waveguides is developed to achieve fully achromatic, broadband, polarizationinsensitive, lossless beam combining. This design may make it po… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 22 publications
0
13
0
Order By: Relevance
“…A tricoupler is fundamentally a device that makes a unitary transform between three electric fields to another three electric fields. We are considering primarily a situation where it is used as a beam combiner with two input beams (with no light injected into the third input) 17 and not as a beam splitter 15 . There are only certain design transformations that are possible.…”
Section: Theoretical Developmentmentioning
confidence: 99%
“…A tricoupler is fundamentally a device that makes a unitary transform between three electric fields to another three electric fields. We are considering primarily a situation where it is used as a beam combiner with two input beams (with no light injected into the third input) 17 and not as a beam splitter 15 . There are only certain design transformations that are possible.…”
Section: Theoretical Developmentmentioning
confidence: 99%
“…It is found that the most efficient taper is obtained if θ(z) varies as a Blackman function [28]. We let…”
Section: Advanced Adiabatic Couplermentioning
confidence: 99%
“…The maximum dephasing ∆β max occurs at the positions z = 0 and z = L, where we choose W Gap (0) = W Gap (L) = 850 nm, W Si (0) = 280 nm and W Si (L) = 310 nm to assure complete decoupling between both WGs. It is found that the most efficient taper is obtained if θ(z) varies as a Blackman function [28]. We let…”
Section: Advanced Adiabatic Couplermentioning
confidence: 99%
“…• Nuller design for exoplanet detections at K, L bands. This will impact arrangement of telescopes within 1.2 km baselines to optimize clever nulling schemes (e.g., Hsiao et al, 33 Lacour et al, 34 Martinache & Ireland 35 ). Table 3 contains information on two reference facility architectures for PFI, one is a 12×3 m array and the other a 12 × 8 m array.…”
Section: Reference Pfi Facility Architecture(s)mentioning
confidence: 99%